2011
DOI: 10.2478/v10181-011-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of PCR/RFLP and ERIC PCR techniques for epidemiological study of Haemophilus parasuis infections in pigs

Abstract: Haemophilus parasuis belongs to opportunistic microorganisms of undefined virulence. The purpose of the studies was to compare suitability of PCR/RFLP in our modification and ERIC PCR for epidemiological study of domestic strains of H. parasuis. The results were evaluated taking into account two different aspects: suitability of the tests for isolating the highest possible number of clone groups and subjective evaluation of the method judged with respect to the following criteria: difficulty, availability of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Some H. parasuis isolates were not able to be assayed by using the ERIC-PCR [20] because they gave no or very poor results. Recent studies have found a high diversity of H. parasuis strains isolated in various geographic areas but have not been able to assign a clear correlation between virulence or serovar and ERIC-PCR clusters [19-21]. This conclusion agrees with other H. parasuis ERIC-PCR studies [12,18].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Some H. parasuis isolates were not able to be assayed by using the ERIC-PCR [20] because they gave no or very poor results. Recent studies have found a high diversity of H. parasuis strains isolated in various geographic areas but have not been able to assign a clear correlation between virulence or serovar and ERIC-PCR clusters [19-21]. This conclusion agrees with other H. parasuis ERIC-PCR studies [12,18].…”
Section: Discussionsupporting
confidence: 61%
“…Although ERIC-PCR has recently been extensively used to study the epidemiology of H. parasuis isolates [19-21], the random amplified polymorphic DNA (RAPD) technique has not been utilized for this purpose. However, RAPD has been used to distinguish other gamma-proteobacteria, including Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the above mentioned pathogens, the Haemophilus parasuis (Hps) can also be recovered from the lungs of pigs with pneumonia [1,[7][8][9][10]. In these cases Hps is often isolated along with other bacterial or viral pathogens and, therefore, the role of Hps in producing pneumonia is not clear [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…It could be also isolated from nasal cavity, tonsils and trachea of apparently healthy pigs [8,14]. Under favorable conditions, Hps can cause severe systemic infection characterized by fibrinous polyserositis, arthritis and meningitis [8,11,14]. Factors leading to systemic infection by Hps have not been clarified to date [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the genotyping methods developed to assess the heterogeneity of G. parasuis isolates is enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR), which determines the relationships of G. parasuis isolates by comparing genetic fingerprints (Oliveira, Blackall & Pijoan, 2003; Rafiee et al, 2000). Compared to other genotyping assays, such as restriction fragment length polymorphism, multilocus sequence typing and single-locus sequence typing, ERIC-PCR has higher discriminatory power and lower cost (Jablonski et al, 2011; Olvera, Segales & Aragon, 2007).…”
Section: Introductionmentioning
confidence: 99%